Multiscale Atmospheric Drivers of the April 2023 Cilacap Flood: Insights from Himawari-9 RGB Imagery and Radiosonde Data - Aminuddin, Jamrud; Susanti, Sri; Mardika, Adnan Dendy; Darmawan, Arief (The Physical Society of Indonesia, 2026)
This study analyzes the atmospheric drivers of extreme rainfall during the 27 April 2023 flood event in Cilacap, Indonesia, using satellite, reanalysis, and in situ data. Convective evolution was examined using rainfall records, Himawari-9 cloud-top temperatures, instability indices (CAPE, CIN, KI, TTI), and surface wind fields. Rainfall exceeded 135 mm from the afternoon to nighttime. Satellite observations showed rapid convective growth, with cloud-top temperatures dropping below −75 °C, indicating mature Cumulonimbus clouds. The 24-Hour Night Microphysics RGB imagery revealed convective initiation around 08:00 UTC and intensification during the evening. Atmospheric instability increased prior to the event, with CAPE exceeding 1600 J kg⁻¹ between 09:00 and 12:00 UTC, while CIN decreased below 80 J kg⁻¹. Surface wind analysis identified a strong low-level convergence zone formed by moist onshore flow from the Indian Ocean interacting with inland winds. This convergence provided dynamical lifting that released the stored instability, triggering deep convection that peaked around 15:00 UTC. The results show that the extreme rainfall was driven by the coupling of high thermodynamic instability and local moisture convergence, demonstrating the value of combining NWP products and satellite RGB imagery for diagnosing coastal extreme rainfall.